2010
DOI: 10.1093/eurheartj/ehq437
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural implementation of pre-hospital diagnosis and direct referral for primary percutaneous coronary intervention in patients with acute ST-elevation myocardial infarction

Abstract: Pre-hospital electrocardiographic (ECG) diagnosis and direct referral for primary PCI enables STEMI patients living far from a PCI centre to achieve a system delay comparable with patients living in close vicinity of a PCI centre.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(127 citation statements)
references
References 17 publications
5
113
0
1
Order By: Relevance
“…Accordingly, many studies have made an effort to reduce the door-to-balloon time. Some studies suggest skipping local hospitals in favor of direct referral to PCI-capable hospitals via pre-hospital electrocardiogram diagnosis [8,9]. This strategy is very effective and shows better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, many studies have made an effort to reduce the door-to-balloon time. Some studies suggest skipping local hospitals in favor of direct referral to PCI-capable hospitals via pre-hospital electrocardiogram diagnosis [8,9]. This strategy is very effective and shows better clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that pre-hospital electrocardiographic diagnosis and direct referral to PCI-capable hospitals decrease the time delay in treating patients with STEMI [1,8,9]. Quality improvement strategies have reduced door-to-balloon times for direct-arrival patients with STEMI undergoing primary PCI.…”
Section: Introductionmentioning
confidence: 99%
“…Optimization of prehospital admission logistics to reduce any delay improves outcome [85] and decreases mortality [86] . While acute thrombolysis and primary PCI have improved outcome, recent studies show that further injury occurs early after reperfusion and can continue long afterwards [87,88] emphasizing the need for therapies limiting clinical reperfusion injury in acute ischemic events.…”
Section: Remote Ischemic Conditioning In Unpredictable Ischemiamentioning
confidence: 99%
“…Additional studies have found that patients presenting to rural teaching hospitals also waited longer than those in urban teaching and non-teaching hospitals as well as rural non-teaching hospitals (Aguirre et al, 2008;Sorensen et al, 2011). The increased wait times may be due in part to the effects of working environments seen in rural, often understaffed and resource limited, hospitals that can affect workload and can be further exacerbated due to the additional demands of instruction.…”
Section: Chapter Five: Discussion and Conclusionmentioning
confidence: 99%
“…There are however major barriers to the implementation of widespread use of primary PCI (PPCI). These barriers include, the delay due to the lack of centres capable o f performing PCI and long distances for transport required for access to the procedure (Sorensen et al, 2011).…”
Section: Geography and The Link To Cardiovascular Diseasementioning
confidence: 99%